College Algebra (11th Edition)

Published by Pearson
ISBN 10: 0321671791
ISBN 13: 978-0-32167-179-0

Chapter 1 - Section 1.6 - Other Types of Equations and Applications - 1.6 Exercises - Page 135: 74



Work Step by Step

$\bf{\text{Solution Outline:}}$ To solve the given equation, $ (x-3)^{2/5}=(4x)^{1/5} ,$ raise both sides to the fifth power to get rid of the denominator in the fractional exponent. Then express the resulting equation in the form $ax^2+bx+c=0,$ and use the concepts of factoring quadratic equations to solve the resulting equation. Finally, do checking if the solution satisfies the original equation. $\bf{\text{Solution Details:}}$ Raising both sides to the fifth power, the given equation becomes \begin{array}{l}\require{cancel} \left((x-3)^{2/5}\right)^5=\left( 4x^{1/5} \right)^5 .\end{array} Using the Power Rule of the laws of exponents which is given by $\left( x^m \right)^p=x^{mp},$ the expression above is equivalent to \begin{array}{l}\require{cancel} (x-3)^{\frac{2}{5}\cdot5 }=(4x)^{\frac{1}{5}\cdot5} \\\\ (x-3)^2=4x .\end{array} Using the square of a binomial which is given by $(a+b)^2=a^2+2ab+b^2$ or by $(a-b)^2=a^2-2ab+b^2,$ the expression above is equivalent to \begin{array}{l}\require{cancel} (x)^2-2(x)(3)+(3)^2=4x \\\\ x^2-6x+9=4x \\\\ x^2+(-6x-4x)+9=0 \\\\ x^2-10x+9=0 .\end{array} Using factoring of trinomials, the value of $ac$ in the trinomial expression above is $ 1(9)=9 $ and the value of $b$ is $ -10 .$ The $2$ numbers that have a product of $ac$ and a sum of $b$ are $\left\{ -1,-9 \right\}.$ Using these $2$ numbers to decompose the middle term of the trinomial expression above results to \begin{array}{l}\require{cancel} x^2-x-9x+9=0 .\end{array} Grouping the first and second terms and the third and fourth terms, the given expression is equivalent to \begin{array}{l}\require{cancel} (x^2-x)-(9x-9)=0 .\end{array} Factoring the $GCF$ in each group results to \begin{array}{l}\require{cancel} x(x-1)-9(x-1)=0 .\end{array} Factoring the $GCF= (x-1) $ of the entire expression above results to \begin{array}{l}\require{cancel} (x-1)(x-9)=0 .\end{array} Equating each factor to zero (Zero Product Property), then \begin{array}{l}\require{cancel} x-1=0 \\\\\text{OR}\\\\ x-9=0 .\end{array} Solving each equation results to \begin{array}{l}\require{cancel} x-1=0 \\\\ x=1 \\\\\text{OR}\\\\ x-9=0 \\\\ x=9 .\end{array} Upon checking, $ x=\{1,9\} $ satisfy the original equation.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.